A child's day : a comprehensive analysis of change in children's time use in the UK - Mullan, Killian (Sociology of children and families series., 2020)
We routinely judge how well children are doing in their lives by how they spend their time, yet we know remarkably little about it. This rigorous review of four decades of data provides the clearest insights yet into the way children use their time. With analysis of changes in the time spent on family, education, culture and technology, as well as children's own views on their habits, it provides a fascinating perspective on behaviour, wellbeing, social change and more. This is an indispensable companion to the work of policy makers, academics and researchers, and anyone interested in the daily lives of children. We routinely judge how well children are doing in their lives by how they spend their time, yet we know remarkably little about it. This rigorous review of four decades of data provides the clearest insights yet into the way children use their time. With analysis of changes in the time spent on family, education, culture and technology, as well as children's own views on their habits, it provides a fascinating perspective on behaviour, wellbeing, social change and more. This is an indispensable companion to the work of policy makers, academics and researchers, and anyone interested in the daily lives of children